Peningkatan Hasil Belajar Menggunakan Model Problem Based Learning (PBL) pada Peserta Didik Kelas 5 SD Negeri Kertasari 01 - Nurhayati, Cuci (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
The Purpose of this study is to improve the learning outcomes of 5th graders at SD Negeri Kertasari 01 on the theme 1 Animal and Human Movement Organs Subtheme 1 Animal Movement Organs Learning 1 Integrated Science and Indonesian Language by using the Problem Based Learning (PBL) learning model. The background of this research is that the learning outcomes of students at SD Negeri Kertasari 01 are less than optimal. There are 23 students out of 31 students who score below the KKM, which is below 68 with an average score of 56,5 with these problems, an effort was made to improve learning so that student learning outcomes can increase through classroom action research. The type of research used is Classroom Action Research (CAR) which is carried out in two cycles. Data collection techniques using observation and learning outcomes tests. The results of the study experienced an increase in the percentage of learning outcomes and the learning activities of students who reached the KKM in cycles I and II increased. Teachers should use the Problem Based Learning (PBL) learning model to improve student learning outcomes.